2008
DOI: 10.1016/j.drugalcdep.2007.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Turning k on its head: Comments on use of an ED50 in delay discounting research

Abstract: Delay discounting (DD) describes how the value of a reinforcer decreases as delay to its delivery increases. Relationships between DD and various aspects of drug abuse have been demonstrated reliably. A potential barrier to wider adoption of DD techniques is that results are often expressed in terms that may be too abstract or unfamiliar to a broader audience, particularly when describing or comparing hyperbolic DD functions or values of k. In an effort to potentially make DD results more accessible, the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 30 publications
1
85
0
Order By: Relevance
“…This task directly measures the Effective Delay 50% (ED 50 ) value for a given commodity, a value that is a simple inverse of the discount rate (Yoon & Higgins, 2008). This is done by presenting a series of questions between some amount of a delayed commodity and half that amount available immediately.…”
Section: Methodsmentioning
confidence: 99%
“…This task directly measures the Effective Delay 50% (ED 50 ) value for a given commodity, a value that is a simple inverse of the discount rate (Yoon & Higgins, 2008). This is done by presenting a series of questions between some amount of a delayed commodity and half that amount available immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Parameters were log transformed prior to statistical comparisons (Yoon and Higgins, 2008). Results from the adjusting amount task and the 5-trial adjusting tasks were compared using a Pearson’s product-moment correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…The delay to the larger amount adjusts over five trials based on participant responses. The final delay (i.e., ED 50 ) following these adjustments provides the discounting parameter for that participant (Yoon and Higgins, 2008). Koffarnus and Bickel (2014) demonstrated that this 5-trial adjusting delay task provides similar k s compared to traditional adjusting amount tasks.…”
Section: Introductionmentioning
confidence: 99%
“…ED50 is computed by setting the discounted value of the larger–later reward as 0.5 (half the value of the objective amount of that reward, normalized to 1) and solving for delay D (Yoon & Higgins, 2008). In the context of the Mazur model, the natural log of k typically satisfies parametric modeling assumptions better than the untransformed k ; that is, for the Mazur model, ED50=1k (Yoon & Higgins, 2008), and ln(ED50) = −ln( k ) (Washio et al, 2011). Because statistical inference is generally invariant to linear transformation, inference based on ln( k ) is identical to statistical inference based on ln(ED50) if the Mazur model is adopted.…”
Section: Methodsmentioning
confidence: 99%